2014
DOI: 10.1103/physrevd.89.124014
|View full text |Cite
|
Sign up to set email alerts
|

Self-force on a charge outside a five-dimensional black hole

Abstract: We compute the electromagnetic self-force acting on a charged particle held in place at a fixed position r outside a five-dimensional black hole described by the Schwarzschild-Tangherlini metric. Using a spherical-harmonic decomposition of the electrostatic potential and a regularization prescription based on the Hadamard Green's function, we express the self-force as a convergent mode sum. The self-force is first evaluated numerically, and next presented as an analytical expansion in powers of R/r, with R den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(63 citation statements)
references
References 32 publications
4
56
3
Order By: Relevance
“…Another possibility would be to try to resum the purely integer-order PN series with rational coefficients that enter into the simplification or its remainder, as was done for a (likely considerably simpler) self-force series in [73].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be to try to resum the purely integer-order PN series with rational coefficients that enter into the simplification or its remainder, as was done for a (likely considerably simpler) self-force series in [73].…”
Section: Discussionmentioning
confidence: 99%
“…We note that in Ref. [14], the authors adopt a definition for the self-force that involves a spherical averaging procedure and the smooth part of the Green's function does not contribute to the self-force after this averaging is performed. Thus, their analysis effectively corresponds to choosing the singular field for which W 0 (x, x 0 ) = 0.…”
Section: The Singular Field For Static Charges a Hadamard Green'mentioning
confidence: 99%
“…Moreover, there is as yet no known general prescription or expression for self-forces in higher dimensions. Despite the lack of formal underpinning, there has been considerable recent interest in the self-force in higher dimensions [14][15][16][17] yielding some very unexpected results in odd dimensions. In particular, Beach, Poisson and Nickel [14] calculated the selfforce on a static scalar and electric charge in a 5D black hole spacetime and found that the result depended on the radius of a sphere centered at the charge, which they interpret as the radius of the particle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using the corresponding series representation of the solution, for example, for the calculation of the self force, requires a lot of work which includes mode-by-mode subtraction of the divergences and summation of the obtained series (see e.g. [6]). In some special cases it is possible to use analytical approximations.…”
Section: Jhep04(2015)014mentioning
confidence: 99%